Estimating the size of criminal populations - Rossmo, D. Kim (Journal of quantitative criminology, 1990)
The estimation of total population size for various phenomena of crime is an important factor critical for criminal justice policy formulation and criminological theory development. In this paper, methods are discussed for estimating the size of a criminal population from police records. Capture-recapture analysis techniques, borrowed from the biological sciences, are used to predict the size of population for migrating (or fleeing) fugitives and for street prostitutes. Heterogeneity and behavioral responses to previous police encounters are identified as major complicating factors. The basic problem is that the police records are virtually unaffected by a potentially large pool of cryptic criminals. It is shown how independently collected auxiliary data can address this problem.